2019
DOI: 10.1007/s00426-019-01159-5
|View full text |Cite
|
Sign up to set email alerts
|

Are age-related deficits in route learning related to control of visual attention?

Abstract: Typically aged adults show reduced ability to learn a route compared to younger adults. In this experiment, we investigate the role of visual attention through eye-tracking and engagement of attentional resources in age-related route learning deficits. Participants were shown a route through a realistic virtual environment before being tested on their route knowledge. Younger and older adults were compared on their gaze behaviour during route learning and on their reaction time to a secondary probe task as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 70 publications
6
27
1
Order By: Relevance
“…They also made more fixations that were consequently shorter in duration as they are bound by fixed encoding times. These patterns are not reflective of previous ageing research using other tasks that have reported that ageing is associated with reductions in saccade amplitudes, velocity and frequency (Dowiasch, Marx, Einhäuser, & Bremmer, 2015;Hilton, Miellet, Slattery, Wiener, 2019;Porter et al, 2010;Williams, Zacks, & Henderson, 2009). Consistent with our findings, Açik, Sarwary, Schultze-Kraft, Onat, and König (2010) found that older adults made more fixations when viewing complex visual stimuli.…”
Section: Discussionsupporting
confidence: 74%
“…They also made more fixations that were consequently shorter in duration as they are bound by fixed encoding times. These patterns are not reflective of previous ageing research using other tasks that have reported that ageing is associated with reductions in saccade amplitudes, velocity and frequency (Dowiasch, Marx, Einhäuser, & Bremmer, 2015;Hilton, Miellet, Slattery, Wiener, 2019;Porter et al, 2010;Williams, Zacks, & Henderson, 2009). Consistent with our findings, Açik, Sarwary, Schultze-Kraft, Onat, and König (2010) found that older adults made more fixations when viewing complex visual stimuli.…”
Section: Discussionsupporting
confidence: 74%
“…These results can then be related to patient performance on the RW tests to investigate whether one can predict patients at a high risk of exhibiting spatial disorientation in the RW based on VR alone. In line with our VR-RW model are successful approaches used by recent healthy aging studies including a realistic VR version of a RW town, immersive VR with RW walking, and VR navigation to predict navigation in complex RW environments (Chen et al, 2017;Coutrot et al, 2019;Hilton et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies have quantified the cognitive demand of wayfinding with the dual-task approach. They observed substantial interference between a wayfinding task and another, concurrent task (Lindberg and Gärling, 1982), particularly when the concurrent task required visuo-spatial processing (Garden et al, 2002;Meilinger et al, 2008), and when participants approached an intersection (Allen and Kirasic, 2003;Hartmeyer et al, 2017;Hilton et al, 2020). In accordance with established dual-task reasoning, these results indicate that wayfinding competes with the other task for cognitive resources, mainly for resources related to visuo-spatial processing, and mainly at times when participants must decide which way to proceed across an intersection.…”
Section: Introductionmentioning
confidence: 57%